G539(P) Trainee-led quality improvement in enhancing service in community paediatrics. (27th April 2015) - Ferguson, EC; Enevoldson, CL; Harrison, C; Hashmi, S; Nagmeldin, E; Suri, S
Abstract : Context: We planned to address two key areas of service provision in our secondary level hospital. Firstly, in keeping with many Community Paediatric Departments, our hospital has experienced an increase in the number and complexity of referrals. As a result many families had long waits for consultations. Secondly in our trust safeguarding work had historically represented a large proportion of the acute workload. Problem and Assessment: 1. Child Development Centre (CDC) appointments Long waiting lists for medical appointments were negatively affecting patient care. The department was not compliant with the NICE guidance on the timeframe for assessment of children with possible social communication disorders. Patient satisfaction surveys had also identified this as an area of concern for families. 2. Child Protection Assessments Vulnerable children competed with acute admissions for assessments and were often seen out of hours, when Consultant medical staff were not on site. Social Care had highlighted concerns about long and unpredictable waits for assessments. Intervention: Firstly, trainees in consultation with their consultant supervisors developed a flexible clinical arrangement to target service provision and meet community competencies in the CDC setting. Trainees were expected to complete six CDC clinics during their six month rotation, which were tailored to the trainee's acute rota. Secondly, a daily child protection medical clinic was implemented and delivered by trainees under consultant supervision. Monthly safeguarding peer review meetings were initiated in line with Royal College of Paediatrics and Child Health guidance to provide support and facilitate training in this area. Strategy for change: To instigate and review the response to change, the Plan-Do-Study-Act (PDSA) cycle was used. An initial multi-disciplinary team (MDT) meeting was used to formalise plans and disseminate information, with three monthly MDT feedback meetings planned. Measurement of improvement: During the initial six month period, review of waiting lists has shown that trainee delivered CDC clinics have resulted in a reduction of waiting lists by 56 patients (the equivalent of 0.4 PA Consultant time). Urgent new patient appointments have fallen from 12 to 0, although routine new patient appointments have increased from 45 to 68. Feedback from the MDT is largely positive. Review of child protection referrals has shown that following the instigation of child protection medical clinics the number of assessments occurring out of hours has fallen to 19% compared to 44% previously. 81% of children are now seen at a prearranged time, without delay, compared to approximately 23% previously. Trainees report feeling more supported in carrying out safeguarding work. A repeat CDC patient satisfaction survey and a planned audit of the child protection clinics will provide further feedback on the success of these interventions, which will lead to further action (PDSA). Effects of changes: Developing a flexible approach to encompass trainees' acute commitments, has required meticulous planning. Room availability was an unexpected factor needing close consideration in the plans. Involvement of trainees has required support and supervision both from Consultants, and the wider MDT, thus requiring some changes to their previous practice. Lessons learnt: Managing a change in service provision requires consideration of many different priorities. When trainees take a key role, it ensures the changes work at their level. Message for others: Working within the European Working Time Directive and today's financial constraints, a flexible approach to service provision is necessary. This initiative has highlighted that direct trainee involvement in the design of service delivery can result in significant changes that benefit patients, trusts and trainees alike. Moreover this venture has enhanced community training, as well as providing trainees with valuable experience in management of change.